States at Work Dynamics of African Bureaucracies - Bierschenk, Thomas; Olivier de Sardan, Jean-Pierre (Africa-Europe Group for Interdisciplinary Studies, 2014)
States at Work explores the mundane practices of state-making in Africa by focussing on the daily functioning of public services and the practices of civil servants. Readership: Anthropologists and political scientists, PhD students, and all interested in politics and the state in Africa and beyond as well as in the comparative functioning of public services.